Pre-Service Portfolios: A Base for Professional Growth - Rolheiser, Carol; Schwartz, Susan (Canadian Journal of Education/Revue canadienne de l'éducation, 2001)
We studied first-year teachers who had developed professional portfolios in their pre- service program. Data came from two interviews with 11 graduates. Participants valued the portfolio process, most continuing to maintain their professional portfolios and to use aspects of the process with their students. Two frameworks, “The Portfolio Organizer” and “retell, relate, reflect,” supported portfolio use. Factors affecting continued portfolio implementation included first-year teaching pressures, the influence of other teachers, and external expectations. The first-year teachers experienced a positive change in attitude and acquired confidence as they refined their use of portfolios. L’étude porte sur l’utilisation des portfolios professionnels par des enseignants en formation des maîtres. Les données proviennent de deux entrevues menées auprès de 11 étudiants diplômés. Les participants apprécient la méthode du portfolio ; la plupart les tiennent à jour et en utilisent certains éléments avec leurs élèves. Deux systèmes, « The Portfolio Organizer » et « retell, relate, reflect », favorisent l’utilisation des porfolios. Parmi les facteurs ayant une incidence sur le recours aux portfolios, les auteures mentionnent les pressions inhérentes à l’enseignement lors de la première année, l’influence des autres enseignants et les attentes externes. Au cours de leur première année, les enseignants deviennent plus sûrs d’eux-mêmes à mesure qu’ils raffinent leur utilisation des portfolios.